(untitled) (Italian Review of Legal History, 2023)
The paper follows the development of the notary profession in Venice in the production of private deeds (instrumenta) and public acts (acta). In the Middle Ages, both activities were performed by the clergy. With the advent of the Commune, a Chancery was instituted to archive separately the acta, as well as the instrumenta. A lay Great Chancellor organised clerks who were members of the clergy, and they also wrote private deeds. As the requirements of the notarial activity became stricter, a policy of careful selection was implemented. The two fields of the notarial activity began to differentiate. In 1433, a papal bull forbade priests to work as clerks in secular institutions. It marked the beginning of a turnover in the Chancery staff, the new clerks being chosen among laymen. Close control was kept on Venetian citizenship as the main requisite to access Chancery posts. Similar criteria were applied to private notaries: after some successful tests, in 1514 a procedure for admission to the profession, and a College of Notaries, were finally instituted.